Electrophoretic deposition forming of nickel-coated-carbon-fiber-reinforced borosilicate-glass-matrix composites - Kaya, C; Boccaccini, AR; Chawla, KK (WILEY, 2000)
The present paper introduces a novel processing technique that involves in situ electrophoretic deposition (EPD), followed by pressureless sintering, to produce dense, defect-minimized, carbon-fiber-reinforced borosilicate-glass-matrix composites with a nickel interface, The process relies on the deposition of submicrometer-sized, colloidal charged particles onto unidirectionally aligned nickel-coated carbon fibers. The preparation and characterization of a kinetically stable nanosized borosilicate sol suitable for EPD are described. The most-important EPD processing parameters in the formation of dense, fully infiltrated, green-body compacts are described, and issues that concern the infiltration of very tight carbon fiber preforms are discussed and effectively solved. Using the crack-path-propagation test, the metallic nickel interface is determined to he very effective to improve the composite mechanical performance, in terms of the nonbrittle fracture behavior. Catastrophic track growth is prevented by such mechanisms as constrained plastic deformation of the interface and fiber debonding and pullout. The proposed processing technique has great potential to fabricate defect-minimized and damage-tolerant fiber-reinforced brittle-matrix composites with a ductile interface, Overall, this new approach offers a cost-effective and short-time processing route for the fabrication of continuous-fiber-reinforced ceramic-matrix composites.
Keywords: CERAMIC COMPOSITES; ALUMINA; FILTRATION; SOL; Materials Science